575 Regression by hetIL-15 monotherapy in different mouse breast cancer models correlates with intratumoral infiltration of a novel population of dendritic cells. (10th December 2020) - Karaliota, Sevasti; Stellas, Dimitris; Stravokefalou, Vasiliki; Nagy, Bethany; Bergamaschi, Cristina; Felber, Barbara; Pavlakis, George
Abstract : Background: IL-15 is a cytokine which stimulates the proliferation and cytotoxic function of CD8+ T and NK cells. We have produced and applied the native heterodimeric IL-15 (hetIL-15) on several preclinical models, which have supported the anti-tumor activity of hetIL-15. Based on these results, hetIL-15 has advanced to clinical trials. The objectives of this study were to explore how hetIL-15 shapes the tumor microenviroment and to characterize the interactions between tumor-infiltrating lymphoid and myeloid cells. Methods: We studied the efficacy of locoregional administration of heterodimeric IL-15 (hetIL-15) in two different orthotopic triple-negative breast cancer (TNBC) mouse models, syngeneic for C57BL/6 and Balb/c, respectively. The effects of hetIL-15 on immune cells were analyzed by flow cytometry, immunohistochemistry (IHC) and gene expression profiling. The profile of the novel infiltrated dendritic cell populations was further explored by bulk and single cell RNAseq. Results hetIL-15 resulted in tumor eradication in 40% of treated mice and reduction of metastasis. Subsequent rechallenges with the same cell line failed to generate tumor regrowth, suggesting the development of immunological memory in hetIL-15 treated mice. hetIL-15 promoted tumor accumulation of proliferating and cytotoxic CD8+ T and NK cells. Additionally, peritumoral hetIL-15 administration resulted in an increased tumor infiltration of both conventional type 1 dendritic cells (cDC1s) and of a novel DC population found only in the hetIL-15 treated animals. Phenotypic profile analysis confirmed the expression of several cDC1 specific markers, including CD103 and IRF8 on this DC population.Transcriptomics and flow analysis of intratumoral dendritic cells indicate that the new hetIL-15 induced cells reside preferentially in the tumors and are distinct from cDC1 and cDC2 populations. Both cDC1s and the novel DC population were inversely correlated with the tumor size. Conclusions: Locoregional administration of hetIL-15 results in complete eradication of EO771 and significant reduction of 4T1 primary breast cancer tumors, prolonged survival and long-lasting specific anti-tumor immunity. hetIL-15 increases the tumor infiltration of activated T and NK cells and intensifies the tumor infiltration of conventional type 1 dendritic cells (cDC1) and a new population of dendritic cells. We propose that the anti-cancer activity of hetIL-15 in primary EO771 tumors is orchestrated by the interplay of NK, CD8+T cells, cDC1 and a novel subset of DCs with a distinct phenotypic profile. These findings suggest a role for hetIL-15 in the treatment of breast cancer. Ethics Approval: The study was approved by the National Cancer Institute-Frederick Animal Care and Use Committee, approval number 19–324 and was conducted in accordance with the ACUC guidelines and the NIH Guide for the Care and Use of Laboratory Animals.